Computed Tomography Images of Entrapped Epidural Catheter. Issue 5 (1st September 2002) - Dam-Hieu, Phong; Rodriguez, Victor; Cazes, Yannick de; Quinio, Bertrand
Abstract : Objective: Knotting and looping of catheters in the epidural space occur rarely. Visualization of a catheter by radiograph or fluoroscopy is not always possible and often inaccurate in locating the knot and/or the loop with precision. We report the case of an entrapped lumbar epidural catheter. Computed tomography (CT) clearly showed a knotted and looped catheter. Case report: A 27-year-old woman underwent epidural analgesia during labor. The epidural catheter was inserted 7 cm into the epidural space. After unsuccessful attempts at removing the catheter, a CT scan was performed, and it showed a catheter knot in the epidural space as well as a loop within the interlaminar ligamentum flavum between L3 and L4. This explained why attempts to remove the catheter by manual traction failed. Surgical removal of the catheter was subsequently performed. Conclusions: CT is useful in showing an entrapped epidural catheter and the mechanisms of entrapment. Surgery should be considered when gentle traction fails to retrieve the catheter. CT allows the clinician to localize the catheter with accuracy, thus facilitating surgical follow-up.